FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN SEKTOR AGRICULTURE - Tia Marsela; Hendra Hendra (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
The purpose of this study is to examine and analyze empirically the effect of dividend policy, liquidity, tangibility, asset turnover, and company growth toward capital structure.The objects used in this study are agriculture sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2020. The sampling technique used was purposive sampling. Sampling with certain criteria, there are 7 companies and 49 data. The data were analyzed using descriptive statistics and panel data regression with a fixed-effect model to test the hypothesis.The results of this study indicate that liquidity has a negative effect on capital structure. This is because the company which have higher liquidity certainly will reduce their own debts and using internal funding. Meanwhile, dividend policy, tangibility, asset turnover, and company growth have no effect on capital structure.